Metode Peningkatan Kekuatan Lentur Material Komposit Resin Polyester yang diberi Penguat Serat Bambu - Nusyirwan; Mutya Rani; Muhammad Surya (Universitas Proklamasi 45, 2025)
One of the polymer materials widely used as a matrix material in the manufacture of composites is unsaturated polyester, which is widely used in engineering fields such as ships, vehicles and also widely used in engineering fields in general. This polyester material for direct use in the construction field still has low mechanical strength and cannot experience good tensile deformation, and is difficult to experience bending loads and can break if it gets a large amount of flexibility. To increase its bending strength, this polyester material is mixed with reinforcing material from bamboo fibre material, which is first refined with various percentages of the mixture ranging from 10% to 30%. After mixing, flexural testing is carried out by applying a flexural load in the middle of the test sample and both ends of the sample are supported with flexural strength that increases along with the resistance of the test material. From the research for flexural testing, it was found that a polyester polymer mixed with bamboo fiber with a percentage of 20% obtained a maximum flexural stress value of σ = 97.35 MPa. When compared with the value of the pure polyester flexural stress of σ = 37.29 MPa, there was an increase in flexural strength of 261.16%.